2020
DOI: 10.1080/13632469.2019.1690599
|View full text |Cite
|
Sign up to set email alerts
|

Damaging Behavior of Masonry Arch Bridges: Analysis of ‘Ponte delle Torri’ in Spoleto, Italy

Abstract: Damage eects on the dynamic response of the masonry bridge 'Ponte delle Torri' in Spoleto are investigated. To model ancient masonry material response, a scalar damage variable is introduced in the stress-strain law, whose evolution is driven by a nonlocal strain measure. A 3D nite element formulation is used. Bridge natural frequencies and modal shapes are evaluated and compared with experimental results. Then, the nonlinear step-by-step dynamic analysis of the entire bridge and an equivalent pier is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…By the way, the study here presented, which is focused on an equivalent single pier, allows for obtaining information only on the out-of-plane response of the overall bridge and is a suitable choice if the attention is mainly focused on this behavior. As shown in Reference [10], a very good match is obtained when the response of the equivalent pier is compared to that of the bridge, both in the linear elastic and nonlinear field, depending on the frequency content of the applied seismic signal. When the first out-of-plane mode of the bridge is mostly excited, the analysis performed on the single pier gives suitable information in terms of out-of-plane displacement history, acceleration, and damaging paths.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…By the way, the study here presented, which is focused on an equivalent single pier, allows for obtaining information only on the out-of-plane response of the overall bridge and is a suitable choice if the attention is mainly focused on this behavior. As shown in Reference [10], a very good match is obtained when the response of the equivalent pier is compared to that of the bridge, both in the linear elastic and nonlinear field, depending on the frequency content of the applied seismic signal. When the first out-of-plane mode of the bridge is mostly excited, the analysis performed on the single pier gives suitable information in terms of out-of-plane displacement history, acceleration, and damaging paths.…”
Section: Introductionmentioning
confidence: 61%
“…This method, although computationally expensive, has recently taken hold to study the complex dynamic behavior of masonry arch bridges, as this represents the most advanced deterministic analysis tool available. Usually, artificial or natural earthquake time histories are selected on the basis of the seismic characteristics of the specific site and its design response spectrum [3,7,10,11]. Moreover, first attempts to apply the Incremental Dynamic Analysis (IDA) to masonry bridges should be mentioned [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although an extensive review of the state of the art on the subject is not the aim of this paper, several investigations and studies can be found in the technical literature; in most cases these studies are aimed at monitoring the state of the infrastructures in order to assess their safety. The classical studies in the structural field aimed at evaluating the mechanical behavior of the artifacts, the characterization and state of conservation of the component materials, their seismic vulnerability and structural modeling for the safety of road and railway bridges [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%